Waktu, Materi, Dan Ruang: Kisah Penciptaan Dalam Perspektif Kejadian 1:1-31 (Jurnal Pendidikan Agama dan Teologi, 2023)
Abstract.This article explores the creation story in Genesis 1:1-31 and provides a deeper understanding of how time, matter and space play a role in creation. Through the time perspective, we can understand that God created everything in six days and rested on the seventh day. The material perspective discusses the materials of the creation of the universe and life that show God's greatness in creating everything. Meanwhile, the spatial perspective explains the position of the Earth and the universe in the creation story.This paper also discusses how humans can understand and appreciate God's creation through this creation story. As God's created beings, humans should be able to appreciate God's greatn ess and care for His creation. The implication of understanding God's greatness in the creation story is to strengthen our faith as human beings and inspire us to care for the environment as part of our responsibility as God's creatures.